KEDUDUKAN ANAK ANGKAT DALAM PERSPEKTIF HUKUM PERDATA, HUKUM ADAT, DAN HUKUM ISLAM - Zamzami, Zamzami (Nurani, 2017)
The title of this article is “The status of adoption a child incivil law, traditional law, and Islamic law.” Adoption is the act ofestablishing a person as parent one who is not in fact or in law hischild. The purpose of this article to compare status of child adoptionthrough civil law, traditional law, and Islamic law. The form of thisresearch is a normative legal search. The method used is the lawapproach and comparative approach. Source data for the article iscollected from civil law literatures, traditional law literatures, andIslamic law literatures about adoption of child. The conclusion of thisexplanation that civil law does not provide for the appointment andadopted a child, but another law – like the child guaranty law statusthe adopted child. In Indonesian’s traditional law status and adopted achild is not same or different between one society law with another. InIslamic law is not known the adopted child